Exploring the scientific philosophy and application of the Langlands program: Circular Logarithm Algorithm: Unrelated Mathematical Models are Solved in the 0 to 1 Interval - Wang, Yiping (British Journal of Healthcare and Medical Research, 2019)
I explore the scientific philosophy of the Langlands program."Mathematical relativity" I define arbitrary functions (groups, clusters, algebraic integer equations and circular logarithmic equations) as a finite number of non-repetitive combination-exchange-aggregation of infinite uncertain "element-factor". I prove symmetry and asymmetry, unity, isomorphism, relative symmetry, zero point, parallel/serial, equivalent permutation, normalization etc. of the Reciprocity Theorem. I establish circular Logarithmic equation with the eccentric elliptic function as base and perform arithmetic solution of the unrelated mathematical model within [0 to 1] interval. The Circular Logarithm Algorithm has extensive and close links with many fields, ranging from mathematical modeling of cosmic evolution, quantum computing, neuromorphic calculation and blockchain to the scientific field of architecture chip simplification.